Antioxidant and anticholinesterase activities of essential oil of Alseodaphne peduncularis meisn - Salleh, W. M. N. H. W. (Turkish Pharmacists Association, 2016)
This study was designed to investigate the antioxidant and anticholinesterase activities of the essential oils from Alseodaphne peduncularis Meisn. GC and GC/MS analysis of the leaves oil showed thirty one components representing 72.6% of the oil. The most abundant components were β-caryophyllene (24.0%), δ-cadinene (15.9%) and germacrene B (12.2%). The antioxidant activity was determined by DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging and total phenolic content assays, while anticholinesterase activity assessed by measuring inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. The essential oil showed weak activity in the DPPH radical scavenging (IC50 of 253.2 µg/mL) and phenolic content (32.5 mg GA/g), while moderate inhibition activity against AChE (I: 45.2%) and BChE (I: 48.6%).